This preview shows page 1. Sign up to view the full content.
Unformatted text preview: 2 B. 9x3 (3x2 ) − 4x2 (2x) (c) If g (x) = (4π + π 2 )10 , then g (x) =
A. 0 B. 10(4π + π 2 )9 (4 + 2π ) C. (d) If h(x) =
A. C. 27x2 − 8x + π 2 )11 D. 4 D. 9 + 3x2 − 4 − 2x + 2 D. Undeﬁned 1
, then h (x) =
4x + x2 1
4 + 2x (e) If f (t) = 1
11 (4π C. 3 B. −4x−2 − 2x−3 1 + t2 , then f (3) = C. (4x + x2 ) − (4 + 2x)
(4x + x2 )2 D. 1
√
2 10 C. 3
A. √
10 B. −(4 + 2x)
(4x + x2 )2 √ 10 D. −505 2. (5 points) Find the equation for the tangent line to the curve y = x2 at x =...
View
Full
Document
This document was uploaded on 03/14/2014 for the course MATH 6 at Long Island U..
 Spring '13
 Dr. Corbett Redden
 Math, Calculus

Click to edit the document details